A Smart Cyclic Azobenzene as Pendant Groups on Polymer Chains: Topological Effect of the Cyclization on Thermal and Photoresponsive Properties of the Azobenzene and the Polymer. Issue 6 (15th April 2013) - Li, Jiangyu; Zhou, Nianchen; Zhang, Zhengbiao; Xu, Ying; Chen, Xinrong; Tu, Yingfeng; Hu, Zhijun; Zhu, Xiulin
<x xml:space="preserve">Abstract</x> Put a ring on it: A cyclic azobenzene has a much higher melting point, stronger fluorescence, and better film‐forming and SRG‐formation ability than its linear precursor. Pcyclic‐AzoMMA, with cyclic azobenzene pendant groups, has a much higher Tg value (100 °C) than Plinear‐AzoMMA, with linear pendants groups (58 °C), and the modulation depth of the photoinduced SRG of Pcyclic‐AzoMMA is thirty times larger than that of Plinear‐AzoMMA.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>